Who's in Charge? : Ownership and Conditionality in IMF-Supported Programs - Boughton, James (IMF Working Papers; Working Paper ;, 2003)
IMF lending is conditional on a country's commitment to carry out an agreed program of economic policies. Unless that commitment is genuine and broadly held, the likelihood of implementation will be poor. Is there a conflict between national commitment and conditional finance? Are national authorities or other agents in the country less likely to "own" a reform program simply because it is conditionally financed? This paper argues that potential conflicts are reduced when program design takes the country's interests and circumstances into account and when conditionality results from a genuine process of interaction between the IMF and the borrower.